DAKWAH SUFISTIK PONDOK PESANTREN AR-RAHMAN DALAM MENGATASI PROBLEM KEJIWAAN MASYARAKAT PALEMBANG - Mohd. Aji Isnaini (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2018)
Abstract: Sufistic da'wah is one of the paths of da'wah which was hacked by the early generation to Islamize people and strengthen their faith. Sufism not only developed as a unique approach to God, but also succeeded in presenting the depths of Sufism in a brilliant literal literary form. Then it is interesting to study that Islamic Boarding School Rehabilitation of Ar-Rahman is also indirectly in the therapy of his patients, also using the Sufism approach. Therefore, the purpose of this study. First, to find out how Sufistic preaching was implemented in the Ar-Rahman Palemban Islamic Boarding School. Secondly, to find out the community's response to the Sufistic preaching of the ArRahman Islamic Boarding School in Palembang. Third, this research can be a reference in making new policies for the development of better Sufistic propaganda. Judging from the object of study and the orientation to be achieved, this study is a field study that uses qualitative methods, with a focus on the analysis of Sufistic preaching of the Ar-Rahman Islamic Boarding School in dealing with the psychiatric problems of the Palembang community. Whereas, the sufistic approach carried out by the Ar-Rahman Islamic Boarding School is through the approach of oral dhikr, dzikir hati, and dzikir deeds. Based on the explanation that has been described, it can be concluded that the results of this study are related to sufistic therapy at Ar-Rahman Islamic Boarding School. The sufistic therapy is applied at the Ar-Rahman Rehabilitation Islamic Boarding School. First, dhikr is done verbally by pronouncing the lafadz